Photoelectrochemical sensor based on Au/Fe3O4 for ultrasensitive detection of uric acid corresponding to alzheimer’s disease - Wang, Xin; Wu, Bin; An, Jian; Cai, Yan (Frontiers in Chemistry, 2026)
IntroductionUric acid (UA) is a crucial biochemical indicator in the human body. The dynamic balance between its production and excretion is essential for maintaining homeostasis, and detecting UA concentration enables disease diagnosis. To address the limitations of traditional UA detection methods, such as high cost and complex operation, this study constructed a photoelectrochemical (PEC) sensor modified with Au/Fe3O4.MethodsFe3O4 and Au nanoparticles (Au NPs) were synthesized via hydrothermal methods, and the Au/Fe3O4 composite was prepared by ultrasonically loading Au NPs onto the surface of Fe3O4.ResultsUnder visible light illumination, the Au/Fe3O4 composite exhibited a significant photocurrent response to UA, primarily due to the synergistic effect between the localized surface plasmon resonance (LSPR) induced by Au NPs and the photogenerated electron–hole pairs from Fe3O4. This synergy promotes the redox reaction of UA at the electrode surface, thereby enhancing the photocurrent signal. Under optimized conditions, the Au/Fe3O4/GCE showed a good linear relationship in the range of 0–100 μmol/L with a detection limit as low as 3.3 μmol/L (S/N = 3).DiscussionThe sensor demonstrated excellent anti-interference ability and stability, offering a new approach for UA detection. This method holds promise for practical applications in clinical diagnosis and bioanalysis.